(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Artificial Intelligence (AI) is becoming increasingly prevalent in the field of research. Recently, AI’s advancements reached new heights with the release of a large language model called ChatGPT, developed by OpenAI1. Based on GPT (Generative Pre-trained Transformer) architecture, it generates human-like responses to text-based prompts in a quick and efficient manner. With AI powered tools like ChatGPT, researchers can now generate ideas more quickly and conduct literature reviews that are more comprehensive and grammatically accurate. Furthermore, these chatbots are invaluable in serving as a writing tool, manage citations, editing and proofreading, and translating content into multiple languages.